Spillway Gate Operation Using Fuzzy System For Dam Control And Operation Support - Nur Nabilah, Zakaria (2023)
Spillway gate operation is a critical aspect of dam control and operation support, ensuring the efficient management of water flow and preventing potential risks such as flooding. In this study, a fuzzy system approach is proposed to enhance the control and operation of spillway gates in dams. The objective of this research is to develop a fuzzy logic-based system that can accurately determine the optimal opening and closing of spillway gates based on various input parameters. Fuzzy logic enables the representation and handling of imprecise and uncertain information, making it suitable for dealing with the complexities of dam operations. The proposed fuzzy system utilizes inputs such as reservoir water level, flow rate, and rainfall to calculate the appropriate gate opening or closing actions. The results will be evaluated based on criteria such as spillway gate efficiency and water level control.